2023
DOI: 10.3390/ijms24119259
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cobra Cardiotoxins on Intracellular Calcium and the Contracture of Rat Cardiomyocytes Depend on Their Structural Types

Abstract: Cardiotoxins (CaTx) of the three-finger toxin family are one of the main components of cobra venoms. Depending on the structure of the N-terminal or the central polypeptide loop, they are classified into either group I and II or P- and S-types, respectively, and toxins of different groups or types interact with lipid membranes variably. While their main target in the organism is the cardiovascular system, there is no data on the effects of CaTxs from different groups or types on cardiomyocytes. To evaluate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…Thus, CTs with a higher charge will possess higher activity. A recent study of the cytotoxic activity of five CTs (CT1No, CT1Na, CT1Nan, CT2No, and CT2Nan, belonging to groups 5, 5, 1, 8, and 3, respectively) against rat cardiomyocytes is in line with this observation [119]. Four CTs (CT3Nk, CT1No, CT2bNsp, and CT2No from groups 5, 5, 8, and 8) were tested against the infusoria Tetrahymena pyriformis [127].…”
Section: Role Of Membrane Activity and Net Electrical Charge Of Cts I...supporting
confidence: 63%
See 1 more Smart Citation
“…Thus, CTs with a higher charge will possess higher activity. A recent study of the cytotoxic activity of five CTs (CT1No, CT1Na, CT1Nan, CT2No, and CT2Nan, belonging to groups 5, 5, 1, 8, and 3, respectively) against rat cardiomyocytes is in line with this observation [119]. Four CTs (CT3Nk, CT1No, CT2bNsp, and CT2No from groups 5, 5, 8, and 8) were tested against the infusoria Tetrahymena pyriformis [127].…”
Section: Role Of Membrane Activity and Net Electrical Charge Of Cts I...supporting
confidence: 63%
“…The proposed classification of CTs extends their division into either P- or S-types, made by Wu WG et al about 30 years ago [ 112 ]. Since then, due to an absence of alternatives, this division has been used by researchers while comparing cytotoxic and other activities of CTs [ 61 , 114 , 115 , 116 , 117 , 118 , 119 ]. Wu WG et al investigated the membrane activities of nine CTs (CT1Ns, CT1Na, CT2Na, CT3Na, CT4Na, CT1Nm, CT2Nm, CT4Nm, and CT5Nm) ( Table 2 ) and one CLBP A5 ( Table S2 ).…”
Section: Classification Of Cts According To Their Membrane Activitymentioning
confidence: 99%
“…However, recent works at IBCh, in collaboration with other institutes of RAS, showed that this activity is also dependent on the structural types of cardiotoxins [ 81 , 82 ]. These differences were observed in the whole heart [ 82 ], isolated muscle and aorta [ 81 ], as well as in cardiomyocytes [ 83 ]. It was shown that the effect of cytotoxins on the cardiovascular system was mainly associated with the disruption of the transport systems responsible for Ca 2+ influx [ 81 ].…”
Section: Other Snake Venom Toxinsmentioning
confidence: 99%
“…The immune system is also influenced by these toxins; for example, complement is depleted by the cobra venom factor [4]. The manuscripts submitted to this Special Issue uncover the molecular mechanisms of animal toxin effects on the cardiovascular [5] and immune [6] systems.…”
mentioning
confidence: 99%